Pengaruh Literasi Keuangan Terhadap Kesejahteraan Keuangan Melalui Perilaku Keuangan Sebagai Variabel Mediasi pada Anggota Koperasi Karyawan - Suci Rahmadani; Vera Intanie Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Financial well-being has become an essential aspect of individual welfare, particularly amid increasing economic uncertainty and the growing complexity of financial products and services. Although financial inclusion in Indonesia has improved considerably, the level of financial literacy remains relatively low, limiting individuals' ability to make informed financial decisions. This study investigates the influence of financial literacy on financial well-being, with financial behavior serving as a mediating variable among employee cooperative members. A quantitative research design was employed using a survey of 187 respondents selected through purposive sampling. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that financial literacy has a positive and significant effect on both financial behavior and financial well-being. In addition, financial behavior significantly enhances financial well-being and partially mediates the relationship between financial literacy and financial well-being. The stronger indirect effect compared with the direct effect suggests that financial knowledge contributes more effectively to financial well-being when it is translated into responsible financial behavior. These findings provide empirical evidence highlighting the strategic role of financial behavior in improving financial well-being and offer practical insights for employee cooperatives in developing more effective financial education programs for their members.